2019
DOI: 10.3389/fimmu.2019.02529
|View full text |Cite
|
Sign up to set email alerts
|

Long Non-coding RNAs Genes Polymorphisms and Their Expression Levels in Patients With Rheumatoid Arthritis

Abstract: Long non-coding RNAs (lncRNAs) are increasingly recognized to play important roles in multiple autoimmune diseases. This study aimed to evaluate the association of four lncRNAs (ANRIL, lnc-DC, MALAT1, ZFAS1) genes single nucleotide polymorphisms (SNPs) with susceptibility to rheumatoid arthritis (RA) patients, as well as their expression levels. Seventeen SNPs of the four lncRNAs were genotyped in a cohort of 660 RA patients and 710 controls using improved multiple ligase detection reaction (iMLDR). The lncRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 44 publications
(45 reference statements)
1
16
0
Order By: Relevance
“…Zhang et al indicated rs4102217 and rs591291 SNPs were not associated with susceptibility of rheumatoid arthritis [37]. The Study of association with HCC have shown rs4102217 had a 1.32-fold risk in the dominant model, and rs591291 highlighted better prognosis in female and HBV negative subgroups, but association between MALAT1 haplotype (rs4102217-rs591291-rs11227209-rs619586) and HCC risk were not observed [23].…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al indicated rs4102217 and rs591291 SNPs were not associated with susceptibility of rheumatoid arthritis [37]. The Study of association with HCC have shown rs4102217 had a 1.32-fold risk in the dominant model, and rs591291 highlighted better prognosis in female and HBV negative subgroups, but association between MALAT1 haplotype (rs4102217-rs591291-rs11227209-rs619586) and HCC risk were not observed [23].…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, the study of rs600231 A>G variant with risk of diseases have been rarely reported, but rs4102217 and rs591291 SNPs were evaluated in diseases. Zhang et al indicated rs4102217 and rs591291 SNPs were not associated with susceptibility of rheumatoid arthritis [37]. The Study of association with HCC have shown rs4102217 had a 1.32-fold risk in the dominant model, and rs591291 highlighted better prognosis in female and HBV negative subgroups, but association between MALAT1 haplotype (rs4102217-rs591291-rs11227209-rs619586) and HCC risk were not observed [23].…”
Section: Discussionmentioning
confidence: 99%
“…At present, studies on rs600231 A > G variant with disease have not been reported, but rs4102217 and rs591291 SNPs were evaluated in rheumatoid arthritis (RA) and HCC. Zhang et al indicated rs4102217 and rs591291 SNPs were not associated with RA susceptibility [35]. Studies of association with HCC have shown rs4102217 had a 1.32-fold risk in the dominant model, and rs591291 highlighted better prognosis in female and HBV negative subgroups, but association between MALAT1 haplotype (rs4102217-rs591291-rs11227209-rs619586) and HCC risk were not found [22].…”
Section: Discussionmentioning
confidence: 99%